Nikolaj Evreinov & others "The storming of the Winter Palace" - Arns, Inke 1968-; Čubarov, Igorʹ 1965-; Sasse, Sylvia 1968- (Diaphanes, 2016)
In 1920, the third anniversary of the October Revolution, the 'Storming of the Winter Palace' was performed with a cast of 10,000. The mass spectacle, directed by Nikolai Evreinov, was a kind of false, deceptive reenactment. It was intended to recall something - the storming of the Winter Palace as the beginning of the revolution - that it itself produced as a theatrical medium. This volume reconstructs the event with texts, photographs, and drawings, and shows how not only in the Soviet Union did the photograph of the theatrical "storming" became a historical document of the October Revolution